Global talent management and staffing in MNEs - Guo, Ying, 1967-; Rammal, Hussain G.; Dowling, Peter J. (International business and management series ;, 2016)
Attracting, managing and retaining talented employees is an important area of human resource management. Managing talent across an organization's global network presents many challenges including expatriation and repatriation issues, cross-cultural adjustment of employees, and operating in different regulatory and economic environments. This volume provides insights into multinational enterprises' (MNEs) global staffing and global talent management (GTM), and covers issues of global mobility from organizational, individual and contextual perspectives. The chapters in this edited volume cover historical development of expatriation, use of self-initiated and company-assigned expatriates, talent management in entrepreneurial firms, and talent retention through effective expatriation and repatriation programs in transitioning and emerging economies.